Dosimetric and workflow evaluation of first commercial synthetic CT software for clinical use in pelvis. (17th March 2017) - Tyagi, Neelam; Fontenla, Sandra; Zhang, Jing; Cloutier, Michelle; Kadbi, Mo; Mechalakos, Jim; Zelefsky, Michael; Deasy, Joe; Hunt, Margie
Abstract: To evaluate a commercial synthetic CT (syn-CT) software for use in prostate radiotherapy. Twenty-five prostate patients underwent CT and MR simulation scans in treatment position on a 3T MR scanner. A commercially available MR protocol was used that included a T2w turbo spin-echo sequence for soft-tissue contrast and a dual echo 3D mDIXON fast field echo (FFE) sequence for generating syn-CT. A dual-echo 3D FFE B 0 map was used for patient-induced susceptibility distortion analysis and a new 3D balanced-FFE sequence was evaluated for identification of implanted gold fiducial markers and subsequent image-guidance during radiotherapy delivery. Tissues were classified as air, adipose, water, trabecular/spongy bone and compact/cortical bone and assigned bulk HU values. The accuracy of syn-CT for treatment planning was analyzed by transferring the structures and plan from planning CT to syn-CT and recalculating the dose. Accuracy of localization at the treatment machine was evaluated by comparing registration of kV radiographs to either digitally reconstructed radiographs (DRRs) generated from syn-CT or traditional DRRs generated from the planning CT. Similarly, accuracy of setup using CBCT and syn-CT was compared to that using the planning CT. Finally, a MR-only simulation workflow was established and end-to-end testing was completed on five patients undergoing MR-only simulation. Dosimetric comparison between the original CT and syn-CT plans was within 0.5% on average for all structures. The de-novo optimized plans on the syn-CT met institutional clinical objectives for target and normal structures. Patient-induced susceptibility distortion based on B 0 maps was within 1 mm and 0.5 mm in the body and prostate respectively. DRR and CBCT localization based on MR-localized fiducials showed a standard deviation of  <1 mm. End-to-end testing and MR simulation workflow was successfully validated. MRI derived synthetic CT can be successfully used for a MR-only planning and treatment for prostate radiotherapy.